Free-Standing SnO(2)@rGO Anode via the Anti-solvent-assisted Precipitation for Superior Lithium Storage Performance - Jiang, Shuli (Front Chem, 2019)
Metal oxides have been attractive as high-capacity anode materials for lithium-ion batteries. However, oxide anodes encounter drastic volumetric changes during lithium ion storage through the conversion reaction and alloying/dealloying processes, leading to rapid capacity decay and poor cycling stability. Here, we report a free-standing SnO(2)@reduced graphene oxide (SnO(2)@rGO) composite anode, in which SnO(2) nanoparticles are tightly wrapped within wrinkled rGO sheets. The SnO(2)@rGO sheet is assembled in high porosity via an anti-solvent-assisted precipitation of dispersed SnO(2) nanoparticles and graphene oxide sheets in the distilled water, followed by the filtration and post-annealing processes. Significantly enhanced lithium storage performance has been obtained of the SnO(2)@rGO anode compared with the bare SnO(2) anode material. A high charge capacity above 700 mAh g(−1) can be achieved with a satisfying 95.6% retention after 50 cycles at a current density of 500 mA g(−1), superior to reserved 126 mAh g(−1) and a much lower 16.8% retention of the bare SnO(2) anode. XRD pattern and HRTEM images of the cycled SnO(2)@rGO anode material verify the expected oxidation of Sn to SnO(2) at the fully-charged state in the 50th cycle. In addition, FESEM and TEM images reveal the well-preserved free-standing structure after cycling, which accounts for high reversible capacity and excellent cycling stability of such a SnO(2)@rGO anode. This work provides a promising SnO(2)-based anode for high-capacity lithium-ion batteries, together with an effective fabrication adoptable to prepare different free-standing composite materials for device applications.